Investigation of Heat Treatment Effect on Mechanical Properties of High Strength Steel Bolt Material - Kinit, U.; Bozca, M.; Palabiyik, I. M.; Sevinc, A.; Buyukalgan, U. H. (SPRINGER INT PUBLISHING AG, 2014)
The objective of this study is to investigate heat treatment effect on mechanical properties of high strength steel bolt material. All sample bolts were M12 and bolts material were 30MnB4. During heat treatment, quenching and tempering processes were applied to high strength steel bolt material. Stress-strain curves were obtained for each sample steel bolt material for different heat treatment. Mechanical properties of steel bolt material such as yield strength, tensile strength and hardness were determined for different heat treatment. It was concluded that heat treatment is important process to change steel bolt material mechanical properties such as hardness, yield strength and tensile strength etc. By heat treating at different temperature levels it is possible obtain different quality of high strength bolt material.
Keywords: Heat treatment; Mechanical properties; High strength; Steel bolt; Engineering